Cryptographic key exchange protocol with message authentication codes (MAC) using finite state machine - Mat Isa, Mohd Anuar; Ahmad, Miza Mumtaz; Mohd Sani, Nor Fazlida; Hashim, Habibah; Mahmod, Ramlan (Elsevier, 2014)
In this work, we explore the authentication and verification of key exchange protocol using Message Authentication Code (MAC). We propose a new MAC scheme model using input-output automata to protect the integrity of the secret key in the key exchange protocol. Our scheme was devised in reference to the Diffie-Hellman communication protocol model. We divided our MAC protocol into three stages of communication sequences in order to simplify the model and the design of automata machine. In the final result, we combined all stages and represented the protocol as Cryptographic MAC Protocol in the regular language. We have shown that the cryptographic MAC protocol for key exchange protocol can be implemented using finite input-output automata with some small modification of the finite state machine. The proposed protocol would be useful for implementation in a lightweight or a secure smart devices communication in the wireless sensor nodes (WSN) network.